2003
DOI: 10.1103/physrevb.68.220506
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective oxygen isotope effect on the magnetic-field penetration depth in underdopedY0.6Pr0.4B

Abstract: We report site-selective oxygen isotope ( 16 O/ 18 O) effect ͑OIE͒ measurements on the in-plane penetration depth ab in underdoped Y 0.6 Pr 0.4 Ba 2 Cu 3 O 7Ϫ␦ , using the muon-spin rotation technique. A pronounced OIE on the transition temperature T c as well as on ab Ϫ2 (0) was observed, which mainly arises from the oxygen sites within the superconducting CuO 2 planes ͑100% within error bar͒. The values of the corresponding relative isotope shifts were found to be ⌬T c /T c ϭϪ3.7(4)% and ⌬ ab Ϫ2 (0)/ ab Ϫ2 (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
44
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 31 publications
(74 reference statements)
10
44
0
Order By: Relevance
“…It was shown that in optimally doped YBa 2 Cu 3 O 7−δ the planar oxygen mainly (≥ 80 %) contribute to the total OIE on T c . These results were confirmed by Zhao et al [31] and later by Khasanov et al [21]. Both groups [31,21] found that in underdoped Y 1−x Pr x Ba 2 Cu 3 O 7−δ the predominant contribution (100 % within error bar) arises from the oxygen within the superconducting CuO 2 planes [see …”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…It was shown that in optimally doped YBa 2 Cu 3 O 7−δ the planar oxygen mainly (≥ 80 %) contribute to the total OIE on T c . These results were confirmed by Zhao et al [31] and later by Khasanov et al [21]. Both groups [31,21] found that in underdoped Y 1−x Pr x Ba 2 Cu 3 O 7−δ the predominant contribution (100 % within error bar) arises from the oxygen within the superconducting CuO 2 planes [see …”
Section: Introductionmentioning
confidence: 53%
“…The error bars of the "trivial" 16 O pac point (zero isotope shift by definition) indicate the intrinsic uncertainty in the determination of T c and λ ab . After [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that-as outlined above-the theoretical data (solid line) have been obtained by renormalizing t 2 and t 4 , whereas the renormalization of t 1 (dashed line) yields the wrong doping dependence of α O . In addition to this study, also site-selective OIE investigations of Y 1 − x Pr x Ba 2 Cu 3 O 7−δ have been performed, thereby clearly revealing that the planar oxygen atoms contribute dominantly to the total OIE on T c at all doping levels, whereas the contribution of chain and apical oxygen ions is only negligible [32][33][34]. However, these findings do not imply that chain and apical oxygen ions are irrelevant to superconductivity, since their small density of states as compared to the one of the planar oxygen ions leads to a small or even vanishing contribution to the total OIE [35].…”
Section: Isotope Effectsmentioning
confidence: 99%